Ectopic Expression of Ankrd2 Affects Proliferation, Motility and Clonogenic Potential of Human Osteosarcoma Cells - Manuela Piazzi (Cancers, 2021)
Ankrd2 is a protein known for being mainly expressed in muscle fibers, where it participates in the mechanical stress response. Since both myocytes and osteoblasts are mesenchymal-derived cells, we were interested in examining the role of Ankrd2 in the progression of osteosarcoma which features a mechano-stress component. Although having been identified in many tumor-derived cell lines and -tissues, no study has yet described nor hypothesized any involvement for this protein in osteosarcoma tumorigenesis. In this paper, we report that Ankrd2 is expressed in cell lines obtained from human osteosarcoma and demonstrate a contribution by this protein in the pathogenesis of this insidious disease. Ankrd2 involvement in osteosarcoma development was evaluated in clones of Saos2, U2OS, HOS and MG63 cells stably expressing Ankrd2, through the investigation of hallmark processes of cancer cells. Interestingly, we found that exogenous expression of Ankrd2 influenced cellular growth, migration and clonogenicity in a cell line-dependent manner, whereas it was able to improve the formation of 3D spheroids in three out of four cellular models and enhanced matrix metalloproteinase (MMP) activity in all tested cell lines. Conversely, downregulation of Ankrd2 expression remarkably reduced proliferation and clonogenic potential of parental cells. As a whole, our data present Ankrd2 as a novel player in osteosarcoma development, opening up new therapeutic perspectives.